Evaluating joint protection education for people with rheumatoid arthritis - Hammond, Alison (1994)
Joint Protection (JP) education is considered an essential component of therapeutic programmes for Rheumatoid Arthritis (RA) patients. The main emphasis is teaching alternate patterns of movement at affected joints to reduce joint stress, particularly in the hands and wrists (Hand JP). Little has been published investigating patients' knowledge of, attitudes towards and adherence to Hand JP following education. Assessments were developed to evaluate these constructs. Reliability and validity were established. A pretest-posttest trial was conducted with RA patients attending a 4 x 2 hour arthritis education programme, including 2.5 hours of JP over 2 sessions (n = 21). Teaching techniques typical of those current in the UK were used. Adherence was evaluated using the Joint Protection Behaviour Assessment. Subjects were videorecorded performing a standardised kitchen activity (making a hot drink and snack) in their own homes. Hand movements during 20 tasks within this (e.g. turning a tap) were analysed and scored as Correct (5%), Partial (2.5%) or Incorrect (0%) Hand JP behaviours. Maximum score =100%. A significant score increase was determined as 20%. Subjects were kept blind to trial aims. There was no significant behaviour change in the pre-education control phase (median score at assessment 1 = 18.40%, IQR 10.25-35.55%). No significant increase occurred at 6 and 12 week follow ups. Mean score change was +4.01% (SO 10.59%; p = 0.14). No significant knowledge increase occurred. Post-education interviews identified a number of barriers to behavioural change. A cognitive-behavioural JP education programme was developed, using motor learning, recall and adherence enhancement strategies, of 4 x 2 hours, with an optional home visit. A crossover trial was conducted (n = 35). There was no significant difference between treatment phase first (Tl, median 15.00%, IQR 5.15 - 25.60%) and control phase first(C1, median 8.75%, IQR 4.38 - 26.25%; p = 0.47) groups' scores pre-education. Both groups' scores rose significantly at 6 weeks post-education, which was sustained at 18 weeks (Tl: median 52.50%, IQR 31.75 - 65.00%; p = 0.00) (Cl: median 41.25%, IQR 30.00 - 60.23%j p =0.00). A significant increase in knowledge occurred. Factors most associated with behaviour change were: hours of education (8 or more); regular home practice; weaker grip, poorer hand range of movement and less hand pain. These results suggest: current JP education methods are ineffective; and this cognitive-behavioural programme significantly increases Hand JP at 4.5 month follow-up. Having demonstrated adherence can be achieved, it is essential to demonstrate whether any therapeutic benefit results before advocating the widespread use of this approach in practice.